2011
DOI: 10.1093/ntr/ntq247
|View full text |Cite
|
Sign up to set email alerts
|

Complexity of Measuring "Cigar Use" in Adolescents: Results From a Split Sample Experiment

Abstract: Inclusion of BE in current measures of cigar product use may improve product use estimates in at-risk groups. However, better estimation of cigar product use may be accomplished by creating additional items to assess the use of subtypes of cigars.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 18 publications
2
25
0
Order By: Relevance
“…21,22 Such distinctions have important implications to the extent that these subtypes may be associated with different user groups and different patterns of use. For instance, whereas cigarillos were commonly referred to as blunts and discussed in the context of marijuana, in contrast, little cigars were not identified as cigars by the majority of our participants; and other evidence suggests little cigars may be more likely to be used by cigarette smokers, 7 mistaken for cigarettes, and perceived as substitutes for cigarettes.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Such distinctions have important implications to the extent that these subtypes may be associated with different user groups and different patterns of use. For instance, whereas cigarillos were commonly referred to as blunts and discussed in the context of marijuana, in contrast, little cigars were not identified as cigars by the majority of our participants; and other evidence suggests little cigars may be more likely to be used by cigarette smokers, 7 mistaken for cigarettes, and perceived as substitutes for cigarettes.…”
Section: Discussionmentioning
confidence: 99%
“…Some common brands are Black and Mild, Swisher Sweets, Dutch Masters, Phillies Blunts, Prime Time, and Winchester.” Brand names were included due to research indicating LCC use may be underreported without such brand name indicators. 2931 Respondents then were asked which products they had “heard of before taking this survey” and which products they “have ever tried, even just one time.” Those who reported they had tried LCCs then were asked if they had used the product in the past 30 days. Respondents who answered affirmatively to “have ever tried, even just one time” were classified in this study as lifetime LCC smokers and those who answered affirmatively to use of LCCs in the past 30 days were classified as current LCC smokers .…”
Section: Methodsmentioning
confidence: 99%
“…Brand information was included for little cigars, cigarillos, and bidis; e-cigarettes; dip and snuff; chewing tobacco; snus; and dissolvables, because previous research has shown that it increases validity of estimates. 38,39 Once a respondent endorsed ever using a tobacco product, they were labeled as an ever user of that product at all subsequent waves. For simplicity, ever use will be referred to as "use" from this point forward.…”
Section: Methodsmentioning
confidence: 99%